Depth-dose distribution of proton beams using inelastic-collision cross sections of liquid water - Candela Juan, C; Crispin-Ortuzar, M; Aslaninejad, M (2011)
Complete physical processes contributing to the shape of the depth-dose distribution and the so-called Bragg peak of proton beams passing through liquid water are given. Height, width and depth of the Bragg peak through investigation of collisions of the projectile, nuclear processes and stochastic phenomena are discussed. Different analytical models for stopping cross sections which lead to Bragg peak are contrasted. Results are also compared with GEANT4 package simulation. © 2010 Elsevier B.V. All rights reserved.